2003
DOI: 10.1046/j.1365-2133.2003.05476.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lymphomas other than mycosis fungoides in Singapore: a clinicopathological analysis using recent classification systems

Abstract: The predominance of cutaneous T-cell lymphomas in this case series closely matched that reported from east Asia; cutaneous B-cell lymphomas are much less common than in Europe. The EORTC classification, which is designed only for primary cutaneous lymphomas, should be used in conjunction with the WHO classification because of the high prevalence of cutaneous lymphomas as the secondary site of disease from systemic lymphoma. In addition, subcutaneous panniculitis-like T-cell lymphoma is a primary cutaneous lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
(58 reference statements)
1
29
0
Order By: Relevance
“…In a series of 6 adult patients with SPTCL in Singapore, 5 patients developed systemic involvement with an aggressive disease course, requiring the use of multiagent chemotherapy, with a median survival of 7 months from presentation. 26 Although this series was reported before the proposed distinction of SPTCL into a/b or g/d T-cell phenotype, patients with SPTCL in our region may differ from those reported in the Western literature, with regard to the severity and aggressiveness of the condition.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In a series of 6 adult patients with SPTCL in Singapore, 5 patients developed systemic involvement with an aggressive disease course, requiring the use of multiagent chemotherapy, with a median survival of 7 months from presentation. 26 Although this series was reported before the proposed distinction of SPTCL into a/b or g/d T-cell phenotype, patients with SPTCL in our region may differ from those reported in the Western literature, with regard to the severity and aggressiveness of the condition.…”
Section: Discussionmentioning
confidence: 64%
“…1,4,5,7,10,12,24,[26][27][28][29][30][31][32] There are only two previous reports of patients who responded to fludarabinebased chemotherapy. 33,34 There are a few reports of patients who received low-dose systemic chemotherapy, eg, cyclophosphamide, methotrexate, and chlorambucil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] The reported incidence of primary and secondary cutaneous lesions is equally common in both T-and B-cell lymphomas. 1 Their average frequency is 0.3 of 100,000, with 65% T-NHL, 25% B-NHL and 10% true HL or rare cell types. 4,13 The frequency of secondary skin involvement in NHL is 16.2% in the present study, which is very close to the reported incidence of 17%.…”
Section: Discussionmentioning
confidence: 99%
“…1 Skin lesions can be seen in Hodgkin's 2,3 and non-Hodgkin's lymphomas (NHL). [4][5][6][7][8][9][10][11][12] The secondary involvement of skin in lymphoma is rare and is associated with advanced stage and poor prognosis.…”
mentioning
confidence: 99%